2003
DOI: 10.1002/ijc.11028
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation profile of tumor‐associated genes p16, p15, hMLH1, MGMT and E‐cadherin in oral squamous cell carcinoma

Abstract: Aberrant promoter hypermethylation of tumor-associated genes leading to their inactivation is a common event in many cancer types. Using a sensitive restriction-multiplex PCR method, we studied the promoter hypermethylation profile of the p16, p15, hMLH1, MGMT and E-cad genes in oral squamous cell carcinoma (OSCC) of Indians. We analyzed a total of 51 samples for the p15 tumor-suppressor gene and 99 samples for each of the remaining genes. Our studies indicate an incidence of promoter hypermethylation of 23% e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
115
4
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 24 publications
12
115
4
2
Order By: Relevance
“…Our studies indicate that the p16 and E-cadherin are the most preferentially targeted genes for methylation in oral squamous cell carcinoma of Indians. There are already reports of p16 and E-cadherin genes suitable for diagnosis of OSCC in individuals at high risk for this disease [23]. The same high percentage methylation in leukoplakia samples suggests that the methylation of these two genes [Table/ Fig-6] may be an early event in the genesis or progression of oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Our studies indicate that the p16 and E-cadherin are the most preferentially targeted genes for methylation in oral squamous cell carcinoma of Indians. There are already reports of p16 and E-cadherin genes suitable for diagnosis of OSCC in individuals at high risk for this disease [23]. The same high percentage methylation in leukoplakia samples suggests that the methylation of these two genes [Table/ Fig-6] may be an early event in the genesis or progression of oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…These (unpublished) data do not support the view that promoter hypermethylation is a frequent mechanism of downregulated or heterogeneous ecad expression in HNSCC. [55][56][57][58] In fact, Yeh et al 59 reported a lack of correlation between ecad promoter methylation and aberrant protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Although several genes, for example, p14, p15, p16, RASSF1A, VHL, hMLH1, and MGMT, have been reported to be silenced by aberrant DNA methylation, (9)(10)(11)(12)(13)(14)(15)(16) some of them were infrequently methylated in OSCC compared with other tumors. In order to create the b.est possible panel of markers for the prediction of outcome, sensitivity to chemotherapy and radiation, and disease status OSCC, more candidates for tumor-suppressor genes targeted by promoter methylation will no doubt be tested in this disease.…”
mentioning
confidence: 99%